Immunomodulatory Effect of Linezolid on Methicillin-Resistant Staphylococcus aureus Supernatant-Induced MUC5AC Overexpression in Human Airway Epithelial Cells - Kaku, Norihito (American Society for Microbiology, 2014)
Linezolid is the first member of the oxazolidinones and is active against drug-resistant Gram-positive pathogens, such as methicillin-resistant Staphylococcus aureus (MRSA). Additionally, linezolid shows an immunomodulatory effect, such as inhibition of inflammatory cytokine production. In this study, we examined the effect of linezolid on MRSA-induced MUC5AC overexpression in airway epithelial cells. In this study, an MRSA supernatant was used to avoid the direct effect of linezolid on MRSA. MUC5AC protein production was significantly increased with a 40-fold dilution of MRSA supernatant. At the mRNA level, MUC5AC gene expression was significantly increased 6 and 9 h after stimulation. In an inhibition study, linezolid significantly reduced MRSA-induced MUC5AC protein and mRNA overexpression at concentrations of 5 and 20 μg/ml, which were the same as the trough and peak concentrations in human epithelial lining fluid. In an analysis of cell signaling, among the mitogen-activated protein kinase inhibitors, only the extracellular signal-regulated protein kinase 1/2 (ERK1/2) inhibitor reduced the MUC5AC protein production to the same level as that of the control; on Western blot analysis, only ERK1/2 was phosphorylated by the MRSA supernatant. In addition, the ERK1/2 phosphorylation was inhibited by linezolid. MUC5AC and MUC5B are the major barrier that traps inhaled microbial organisms, particulates, and foreign irritants. However, in patients with chronic respiratory diseases, pathogen-induced MUC5AC overexpression causes many problems, and control of the overexpression is important. Thus, this study revealed that linezolid showed a direct immunomodulatory effect in airway epithelial cells.